If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5/6x-4=-6
We move all terms to the left:
5/6x-4-(-6)=0
Domain of the equation: 6x!=0We add all the numbers together, and all the variables
x!=0/6
x!=0
x∈R
5/6x+2=0
We multiply all the terms by the denominator
2*6x+5=0
Wy multiply elements
12x+5=0
We move all terms containing x to the left, all other terms to the right
12x=-5
x=-5/12
x=-5/12
| 8x^2-10x-30=0 | | 16x+6=-2 | | –2s+2=–6 | | 5^(3x+1)=9 | | 0=8x^2-10x+6 | | x^2/0.5=1.8*10^-5 | | 3y+2/5=1/6 | | -2x+4=2x-7 | | 3x^2+24x-40=0 | | 9x-4=8x+21 | | 3.9=0.9x^-0.8 | | 4n²+2n-3=0 | | –10+4d=10+2d | | –8+7g=6+9g | | d-6/17=-2 | | (5x)°=95° | | 2(x2-14)=0 | | 14x-9=61 | | 4.5x+12=6x-3 | | 2x+75=125° | | b=9-7 | | -2=b-16 | | .3b-1=8 | | s2+24s+23=0 | | 0.05y=0.2 | | (4x-12)+(5x)+x=180 | | 13/4x=5/4 | | .8q-88=2q-16 | | B=18aa= | | 2x-1=7x+1 | | 5x+30=x+60 | | -12=1/3(y-18) |